Mental Accounting dan Heuristik: Fenomenologi pada Kolektor Merchandise - Ferrary, Melissa; Ikhsan, Syarbini; Yunita, Khristina; Dosinta, Nina Febriana; Damayanti, Fera (Papanda Publisher, 2024)
The entertainment industry is starting to present various types of merchandise to pamper fans who are members of a community. The consumptive nature of merchandise collectors can have a negative impact if it cannot be controlled properly. This research aims to understand how mental accounting and heuristics are applied to anime merchandise collectors in managing finances and making purchasing decisions. This research uses a qualitative method with a phenomenological approach. The data collection techniques used in this research are structured interviews and in-depth observation. This research uses data analysis techniques in the form of data reduction, data presentation, and drawing conclusions. The results of this research show that anime merchandise collectors have applied mental accounting and heuristics to managing their finances and in making purchasing decisions. Of the eight informants interviewed, each had their own way of managing their finances but had the same goal, namely being able to control impulsive buying.